Gene Mutations Resulting in the Development of ARVC/D Could Affect Cells of the Cardiac Conduction System - Pieperhoff, Sebastian (Frontiers in Physiology, 2012)
In contrast to epithelial cells, cardiomyocytes are connected by complex hybrid-type adhering junctions, termed composite junctions (areae compositae). Composite junctions are found to be composed of typical desmosomal as well as adherens junction proteins. Therefore, in adult mammalian cardiomyocytes desmosomal proteins are not restricted to the relatively small desmosomes but are indirectly involved in anchoring the myofibrillar actin filaments. Subsequent investigations revealed that the formation of composite junctions is a rather late event during mammalian development and vertebrate evolution. Nascent, more round shaped cardiomyocytes of early developmental stages are connected by desmosomes and separate adherens junctions quite similar to cells of epithelial origin. During progression of development both types of adhering junctions seem to gradually fuse at the two poles of the mature mammalian cardiomyocytes to establish the hybrid-type composite junctions. Recently, we could show that the specialized cardiomyocyte derived cells of the cardiac conduction system exhibit high amounts of desmosomes, not fully established composite junctions and adherens junctions. This underlines the fact that cells of the cardiac conduction system are known to resemble cardiomyocytes in their nascent state. However, the astonishing high amount of desmosomal protein containing adhering junctions connecting e.g., Purkinje fibers raises the possibility that pacemaker and conductive tissue may be affected by desmosomal gene mutations in ARVC/D patients.